Mitochondrial Dysfunction: Cause or Consequence of Vascular Calcification? - Phadwal, Kanchan; Vrahnas, Christina; Ganley, Ian G.; MacRae, Vicky E. (Frontiers in Cell and Developmental Biology, 2021)
Mitochondria are crucial bioenergetics powerhouses and biosynthetic hubs within cells, which can generate and sequester toxic reactive oxygen species (ROS) in response to oxidative stress. Oxidative stress-stimulated ROS production results in ATP depletion and the opening of mitochondrial permeability transition pores, leading to mitochondria dysfunction and cellular apoptosis. Mitochondrial loss of function is also a key driver in the acquisition of a senescence-associated secretory phenotype that drives senescent cells into a pro-inflammatory state. Maintaining mitochondrial homeostasis is crucial for retaining the contractile phenotype of the vascular smooth muscle cells (VSMCs), the most prominent cells of the vasculature. Loss of this contractile phenotype is associated with the loss of mitochondrial function and a metabolic shift to glycolysis. Emerging evidence suggests that mitochondrial dysfunction may play a direct role in vascular calcification and the underlying pathologies including (1) impairment of mitochondrial function by mineral dysregulation i.e. calcium and phosphate overload in patients with end-stage renal disease and (2) presence of increased ROS in patients with calcific aortic valve disease, atherosclerosis, type-II diabetes and chronic kidney disease. In this review, we discuss the cause and consequence of mitochondrial dysfunction in vascular calcification and underlying pathologies; the role of autophagy and mitophagy pathways in preventing mitochondrial dysfunction during vascular calcification and finally we discuss mitochondrial ROS, DRP1 and HIF-1 as potential novel markers and therapeutic targets for maintaining mitochondrial homeostasis in vascular calcification.